Predictors of advanced chronic kidney disease in infancy after definitive vesicoamniotic shunting for congenital lower urinary tract obstruction - Katsoufis, Chryso Pefkaros; DeFreitas, Marissa; Leuchter, Jessica; Seeherunvong, Wacharee; Chandar, Jayanthi; Abitbol, Carolyn (Frontiers in Pediatrics, 2022)
Background: Severe congenital lower urinary tract obstruction (cLUTO) is associated with poor postnatal outcomes, including chronic and end stage kidney disease, and high mortality. Studies of the impact of fetal intervention through vesicoamniotic shunting are marred by a device malfunction rate of up to 60%. In this study, we delineate the postnatal course and infant kidney function following definitive urinary diversion in utero. Materials and Methods: This is a retrospective, single-center cohort study of 16 male infants who survived the fetal intervention to birth, from 2010 to 2014 at a single center. All had patent shunts in place at birth. Perinatal and biochemical characteristics were collected with patients followed for one year, or until demise, with serial measures of serum creatinine (SCr) and serum cystatin C (CysC). Results: Of the 16 males, 81% were non-white (38% black, 43% Hispanic). Shunts were placed at a median of 20 weeks (IQR 19,23) gestation, with median fetal bladder volume of 39 cm3 (IQR 9.9,65). All neonates were born preterm (median 34 weeks (IQR 31,35)) and the majority with low birth weight (median 2340 grams (1895,2600)). 63% required positive pressure ventilation. Advanced chronic kidney disease stage 4-5 at 1 year of age was predicted by neonatal characteristics: peak SCr ≥ 2 mg/dL, time to peak SCr > 6 days, discharge SCr ≥ 1.0 mg/dL, CysC ≥ 2.5 mg/L, urine protein:creatinine ≥ 4.8 mg/mg, urine microalbumin:creatinine ≥ 2.2 mg/mg. In infancy, a nadir SCr ≥ 0.5 mg/dL occurring before 160 days (5.3 months) of age was also predictive of advanced chronic kidney disease stage 4-5 at 1 year. Three patients died in the neonatal period, with 1 receiving kidney replacement therapy (KRT). Three additional patients required KRT before 12 months of age. Conclusions: Even with definitive vesicoamniotic shunting for cLUTO, postnatal morbidity and mortality remain high, emphasizing the role of renal dysplasia, in spite of urinary diversion, in postnatal kidney dysfunction. Neonatal and infant biochemical parameters exhibit distinct trends that offer families and physicians a better understanding of the prognosis of childhood kidney function.